2020
DOI: 10.1364/osac.399941
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion-engineered T-type germanium waveguide for mid-infrared supercontinuum and frequency comb generations in all-normal dispersion region

Abstract: In this paper, a T-type Germanium (Ge) waveguide with the all-normal dispersion profile is designed for mid-infrared supercontinuum (SC) and frequency comb generations. The nonlinearity coefficient of the designed waveguide is calculated as 30.48 W -1 •m -1 at the initial pump wavelength of 3.0 μm. Moreover, the group-velocity dispersion is kept low and flat in the considered wavelength range. Simulation results show that with the designed waveguide, the highly coherent and octave-spanning MIR SC can be genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…The 100 independent simulations will be carried out and the average value of each pair of the output fields will be calculated in this work. And the noise is described as [42] ( )…”
Section: Theoretical Modelmentioning
confidence: 99%
“…The 100 independent simulations will be carried out and the average value of each pair of the output fields will be calculated in this work. And the noise is described as [42] ( )…”
Section: Theoretical Modelmentioning
confidence: 99%
“…MIR coherent and broadband SC generation is another hot topic due to its rich application in trace gas sensing, LIDAR, biomedical imaging, etc. In 2018, Singh et al demonstrated octave-spanning and [86]. Some recent works show that ultrabroad SC that covers multi-bands from UVR to MIR can be generated by dispersive wave assistance in specially designed MNPWs.…”
Section: Supercontinuum and Frequency Comb Generationmentioning
confidence: 99%
“…In particular, its large spectral transparency window ranging from 2 to 15 μm, covering the whole molecule fingerprint, and its high refractive index allows the implementation of devices with reduced footprint. In recent years, numerous Ge-based fundamental devices have been developed using Ge-on-silicon [ 3 , 4 ], Ge-on-silicon-on-insulator [ 5 ], Ge-on-Si 3 N 4 [ 6 ], and germanium-on-insulator [ 7 ] platforms.…”
Section: Introductionmentioning
confidence: 99%